2019
DOI: 10.1016/j.bbi.2018.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Enriched environment regulates thymocyte development and alleviates experimental autoimmune encephalomyelitis in mice

Abstract: Environmental and social factors have profound impacts on immune homeostasis. Our work on environmental enrichment (EE) has revealed a novel anti-obesity and anticancer phenotype associated with enhanced activity of CD8+ cytotoxic T lymphocytes in secondary lymphoid tissues. Here we investigated how an EE modulated thymus and thymocyte development. EE decreased thymus mass and cellularity, decreased the double positive thymocyte population, increased the proportion of CD8+ T cells, reduced the CD4:CD8 ratio, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…A major candidate for this stimulus is BDNF, the central coordinator for many CNS and peripheral effects of EE. We previously demonstrated that neuronal overexpression of BDNF reproduces various effects of EE including systemic metabolism, adipose remodeling, immune modulations, cancer, and aging [9][10][11][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…A major candidate for this stimulus is BDNF, the central coordinator for many CNS and peripheral effects of EE. We previously demonstrated that neuronal overexpression of BDNF reproduces various effects of EE including systemic metabolism, adipose remodeling, immune modulations, cancer, and aging [9][10][11][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…We have used a mouse model of environmental enrichment (EE) to study an active lifestyle influence on health and diseases (Cao et al 2004, Cao & During 2012, During et al 2015, Foglesong et al 2016, Xiao et al 2016, 2019, Mcmurphy et al 2018. EE refers to a housing with increased space, physical activity and social interactions that facilitate enhanced sensory, cognitive, motor and social stimulation (Nithianantharajah & Hannan 2006).…”
Section: Introductionmentioning
confidence: 99%
“…One study demonstrated that EE improved chemotaxis of phagocytes and lymphocytes and reduces the oxidative stress in immune cells, which strengthened the responses to infection (Arranz et al, 2010). Ultimately, it was demonstrated that EE, in EAE model, modulates thymus and thymocyte development inducing an enhanced activity of CD8+ cytotoxic T lymphocytes in secondary lymphoid tissues (Xiao et al, 2019). This work provides additional evidence that EE could exert immunomodulatory effects.…”
Section: Discussionmentioning
confidence: 84%
“…Additionally, EE improves remyelination by promoting adult neural progenitor mobilization in the EAE model (Fields, 2008;Magalon et al, 2007). Furthermore, EE enhances CD8+ cytotoxic T lymphocytes activity in secondary lymphoid tissues in EAE (Xiao et al, 2019).…”
Section: Introductionmentioning
confidence: 96%